Morphological, cytochemical, and ultrastructural study of thrombocytes and leukocytes in neotropical fish, Brycon orbignyanus Valenciennes, 1850 (Characidae, Bryconinae) - Tavares-Dias, M.; Moraes, F. R. [UNESP] (My University, 2006)
Morphological, cytochemical and ultrastructural studies are important to demonstrate the function of the blood cells, which is very little understood in teleosts. In peripheral blood of piracanjuba' Brycon orbignyanus, thrombocytes, lymphocytes, monocytes, neutrophils and heterophils were studied and characterized. Thrombocytes had a fusiform or oval shape with PAS-positive granules. Lymphocytes presented small size with sparse basophilic cytoplasm. Monocytes were large in size, presented basophilic cytoplasm that may be foamy or vacuolated, with non-specific esterase staining. The neutrophils presented lightly neutrophilic granule cytoplasm, with positivity for PAS and peroxidase. The heterophils were large in size, with eosinophilic and basophilic granules cytoplasm and PAS-positive. Transmission electron microscopy study demonstrated that the thrombocytes, lymphocytes and monocytes features were similar to other teleosts. In ultrastructural study only one type of neutrophils was observed. Cytochemical findings indicated that neutrophils and monocytes of B. orbignyanus may be involved in phagocytosis, and neutrophils play an important microbicidal role.
Keywords: Brycon orbignyanus cytochemistry; Leukocytes; Thrombocytes ultrastructure; biological marker; animal; cell granule; chemistry; enzyme immunoassay; fish; leukocyte; methodology; monocyte; neutrophil; periodic acid Schiff stain; physiology; thrombocyte; transmission electron microscopy; ultrastructure; Animals; Biological Markers; Blood Platelets; Cytoplasmic Granules; Fishes; Immunoenzyme Techniques; Microscopy, Electron, Transmission; Monocytes; Neutrophils; Periodic Acid-Schiff Reaction; Brycon orbignyanus; Bryconinae; Characidae; Teleostei